Transnational Islam Circulation of religious Ideas, Actors and Practices between Niger and Nigeria - Apard, Élodie (WAPOSO Series, 2020)
At the crossroads of major trade routes and characterised by intense human circulations, the area that encompasses northern Nigeria and southern Niger is a privileged space to study transnational religious dynamics. Islam is, indeed, an essential feature of this region assuming today new forms in terms of discourses, practices, and modes of dissemination. In order to capture their changing complexity and diversity, regional Islamic dynamics need to be observed from both sides of the Niger-Nigeria border, where religious patterns echo each other but also obey different socio-political injunctions. While studying the processes of religious renewal and mutation, it is necessary to pay attention to the varied forms these processes take, to their direct and indirect effects and to the channels of transmission used. An interdisciplinary team of seven researchers from Niger, Nigeria, France and the United Kingdom was set up to conduct this transnational study; all authors carried out ethnographic fieldwork in both countries while constantly exchanging, comparing and discussing their respective findings with each other. Thus, this book provides first-hand material collected in the field, that contributes to enrich the reflexion on contemporary transformation dynamics in the Islamic landscapes of Niger and Nigeria, but also reflects the relevance of a transnational and comparative approach of these phenomena. Finally, it showcases the collaborative work of African and European scholars from Francophone and Anglophone countries - a type of scientific partnership unprecedented in this field.